Devociones y peregrinajes como formas de territorialidad y visibilidad institucional Córdoba (Argentina), 1870-1910 - Gallardo, Milagros (Cordis: Revista Eletrônica de História Social da Cidade, 2021)
The objective of this work is to make an analysis of the spatial dynamics of the Diocesan Church of Córdoba. To do this, we will focus our gaze on two devotions: The Christ of the Good Death of Reduction and the Virgin Consolata de Sampacho. The creation of these poles of religiosity responds to logics of ecclesiastical territorialization, aimed at strengthening the Catholic presence in the rural area of Córdoba at the end of the century, within the framework of a complex process of Romanization of the Church, consolidation of the national State and social change.